Propuesta De Un Modelo De Gestión Para La Prevención De Incendios Forestales En Pinus Radiata En La Comunidad Ganquis Provincia De Chimborazo - Manuel, Espinoza Víctor; María, Quinchuela Pozo Flor; Ximena, Lara Vasconez Norma; Esteban, Espinoza Espinoza Armando (European Scientific Journal, ESJ, 2017)
The objective of this study was to elaborate a management model proposal for the prevention of forest fires in the plantation of Pinus radiata located in the community of Ganquis. The approach of the management model proposal started with a forest inventory and the subsequent identification of the threats and vulnerabilities of the plantation and community. Once the information was collected, next step consisted in determining the indexes of risks to forest fires for which an adaptation was made of the methodology proposed by Sun Mountain International for the analysis of vulnerability at the municipal level raised by UNDP. The results obtained were a historical analysis of the forest fires at the province level in Chimborazo, an inventory of the volume of wood existing in the plantation and 9 potential threats and 10 vulnerabilities at the community of Ganquis and at the plantation of Pinus radiata sorrounding it. With these results the proposal of the management model for the prevention of forest fires was carried out, which has 3 guidelines that are directed to the formation of community fire brigades, prevention actions and establishment of response procedures. It is recommended that at the institutional level a system of forest fire registry be standardized in order to generate the necessary information to carry out more detailed studies on forest fires and their incidence on various natural resources.